Causal role of oxidative stress in age-related macular degeneration: a bidirectional Mendelian randomization study - Li-Yun Yuan; Wang-Ming Su; Liang-Pin Li; Xiao-Feng Tian; Xue-Li Zheng; Xiao-Yong Yuan (International Journal of Ophthalmology)
AIM: To elucidate causal pathways between oxidative biomarkers and age-related macular degeneration (AMD) phenotypes. METHODS: A bidirectional Mendelian randomization (MR) analytical protocol was implemented, which utilized genome-wide association study (GWAS) summary statistics derived from the IEU OpenGWAS repositories. The investigation focused on 11 oxidative stress markers and AMD phenotypes, encompassing both wet and dry subtypes. The MR methodology incorporated inverse-variance weighted (IVW) calculations, MR-Egger statistical regression, weighted median approximation, and weighted mode assessments to estimate causative relationships. Sensitivity evaluations were conducted to verify result robustness and identify potential pleiotropy. RESULTS: Genetically predicted elevated catalase (CAT) concentrations demonstrated significant associations with heightened risks of overall AMD (IVW OR=1.084, 95%CI: 1.021-1.151, P=0.008) and wet AMD phenotype (IVW OR=1.113, 95%CI: 1.047-1.247, P=0.007). Higher genetically predicted albumin concentrations corresponded with reduced AMD risk (IVW OR=0.827, 95%CI: 0.715-0.957, P=0.013) but increased wet AMD risk (IVW OR=1.229, 95%CI: 1.036-1.458, P=0.018). Reverse MR analysis revealed that genetically predicted dry AMD exhibited significant association with reduced albumin levels (IVW OR=0.987, 95%CI: 0.979-0.996, P=0.004), while wet AMD corresponded with decreased total bilirubin (TBIL) and paraoxonase (PON) activity. CONCLUSION: The results offer strong support for a causal link between markers of oxidative stress and the development of AMD, indicating that oxidative processes play a role in driving the disease progression.